Vincristine Induced Neurotoxicity: Study of 75 Cases - Arzanian, M.T.; Mehdizadeh, M.; Zamani, G.R. (Iranian Journal of Child Neurology, 2009)
Objective Concern for side-effects of therapy related to treatment of childhood malignancies is becoming an increasingly important topic. In this study, we evaluated extent of vincristine (VCR) induced neurotoxicity in a group of children who underwent chemotherapy, with VCR being part of the regimen. Materials & Methods In this investigation, for 75 children (54% boys, 46% girls), aged between 1 to 14 (mean 6.5±4.3) years, serial weekly neurological examinations were performed; of the 75, 70 had acute lymphoblastic leukemia and 5 Wilm's tumor. All patients were on a chemotherapy protocol of at least 4 consecutive VCR (1.5mg/m2) injections. Results Decreased deep tendons reflexes were seen in the Achilles reflex in 78%, and the patellar reflex in 53% of patients. Muscle weakness was found in 70% of patients, being mild in 76% of them. Four percent of patients showed severe weakness. Petosis, jaw pain, hoarseness, abdominal pain and constipation were seen in 15%, 6%, 12%, 12% and 12% respectively. Paresthesia was observed in 32 of 52 patients, over 4 years old. No cases of foot drop, urinary retention or facial nerve palsy were seen in this patient group. Conclusion Children on usual doses of vincristine regimen may have neuropathic side effects but most of these side effects are mild and not troublesome.